Understanding adaptability : a prerequisite for effective performance within complex environments - Burke, C. Shawn; Pierce, Linda G.; Salas, Eduardo (Amsterdam ; London : Elsevier JAI, 2006)
Adaptability is becoming a hallmark of effective performance at all levels and types of organizations. As complexity rises within the internal and external environments that organizations operate within, it is no longer acceptable to be able to perform well when things go as expected; instead individuals, teams, and organizations must be able to continuously adapt their knowledge and skills in order to remain competitive in environments which are fluid, often ambiguous, and where multiple pathways to goal attainment exist. Thus, this volume takes a multi-disciplinary approach to increasing ou.
Cover -- Contents -- List of Contributors -- Preface -- Section I: Individual Level -- Individual Adaptability (I-ADAPT) Theory: Conceptualizing the Antecedents, Consequences, and Measurement of Individual Differences in Adaptability -- Adaptability in Modern Work -- Previous Research on Individual Adaptability (Broadly Conceptualized) -- The I-ADAPT Theory -- I-ADAPT Theory -- Comparison of I-ADAPT Theory to Existing Conceptualizations -- The I-ADAPT Measure -- Future Directions and Unanswered Questions -- Conclusion -- Acknowledgment -- References -- Appendix. Short 55-Item I-ADAPT-M -- Adaptability in the Workplace: Selecting an Adaptive Workforce -- A Model of Individual Adaptive Performance -- Individual Differences Predictors of Adaptive Performance -- Cognitive Ability -- Practical Intelligence -- Originality -- Emotional Stability -- Openness -- Cognitive Flexibility -- Achievement Motivation -- Cooperativeness -- Sociability -- Social Intelligence -- Physical Ability -- Linkages Between Individual Adaptability Attributes and Adaptability Dimensions -- Model of Team Adaptive Performance -- Predicting Team Adaptability -- Individual Adaptability -- Team Motivation and Attitudes -- Adaptive Mental Models -- Team Experience -- Team Heterogeneity -- Team Leadership -- Team Type -- Selecting Adaptable Teams -- Selection Measures -- Conclusions -- Notes -- References -- Visualization Tools to Adapt to Complex Military Environments -- Introduction -- RAVENS: A General Cognitive Model -- Adaptiveness and Situational Awareness -- Adaptive Sense-Making: The Value of a Good Story -- Sense-Making: Building Understanding in the Decision Maker -- Visualizing Risk -- Simulation Tool -- Simulation Study Methods -- Results of Simulation Study -- Discussion -- Coevolutionary Algorithms for Peacekeeping Simulations: Visualizing Emergent Solutions -- Overview -- Creating the SASO Environment -- Coevolution of COAs -- Scheherazade: The SASO Simulation -- Visualization -- SASO Simulation Analysis -- Coevolution Analysis -- Conclusion -- References -- Section II: Team Level -- Team Adaptation: Realizing Team Synergy -- Team Adaptation: Realizing Team Synergy -- Teams & Team Context -- Team Adaptation -- Adaptive Team Performance -- Framing Team Adaptation & Adaptive Team Performance -- Adaptive Cycle of Dynamic Processes -- Emergent States -- Individual Characteristics -- Team Characteristics -- Job Characteristics -- Conclusion -- Acknowledgments -- References -- Cultural Adaptability* -- Barriers to Cultural Adaptability -- Cultural Values and Orientations -- Human Relations -- Power Relations -- Rules Orientation -- Time Orientation -- Allocation of Status -- Cognitive Style and Thinking Orientation -- Communication -- Public and Private Space -- Miscellaneous -- Framework for Understandi.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Organizational effectiveness; Adaptability (Psychology); Teams in the workplace; Organizational change; Efficacité organisationnelle; Adaptation (Psychologie); Équipes de travail; Changement organisationnel; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Adaptability (Psychology); Organizational change; Organizational effectiveness; Teams in the workplace